Diversity of endophytic fungi of rice plants in Padang City, Indonesia, entomopathogenic to brown planthopper (Nilaparvata lugens) - TRIZELIA TRIZELIA; HALIATUR RAHMA; MY SYAHRAWATI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Trizelia, Rahma H, Syahrawati M. 2023. Diversity of endophytic fungi of rice plants in Padang City, Indonesia, entomopathogenic to brown planthopper (Nilaparvata lugens). Biodiversitas 24: 2384-2392. Various endophytic fungi can live in plant tissues for all or part of their life cycle without causing damage or disease in their host. Several genera of endophytic fungi have been reported to be entomopathogenic and can be used to control insect pests. This study aimed to determine the diversity of endophytic fungi from rice stems that were entomopathogenic against Nilaparvata lugens (Stål, 1854) or Brown Planthopper (BPH). Endophytic fungi were isolated from rice stems of IR42 and Cisokan varieties grown in Padang City, West Sumatra Indonesia. Isolated fungi were first evaluated for their pathogenicity against Tenebrio molitor larvae. Subsequently high pathogenicity showed isolates were tested on nymphs and adults of BPH. The results showed that the entomopathogenic fungi isolated from IR 42 and Cisokan were the members of genus Aspergillus, Trichoderma, and Beauveria. The entomopathogenic fungi from IR 42 were more diverse than Cisokan, and Beauveria sp. was the most common isolate and had a better ability to kill the BPH. The highest mortality of BPH was found in PIR 1.3 isolate, but the mortality was still relatively low (53.33% nymphs and 34.99% adults). Further study is needed to increase the effectiveness of these endophytic fungi against BPH directly or indirectly by inducing resistance.